TELAAH KRITIS âCOUNTER LEGAL DRAFT KOMPILASI HUKUM ISLAMâ (Reorientasi Fikih Hukum Keluarga Islam Indonesia) - khair, abul (AL-RISALAH, 2016)
The movement of Islamism and modernization in the field of Family Law in Indonesia did not stop after the regulated on the Compilation of Islamic Law (KHI).